Side Effects of Curcumin: Epigenetic and Antiproliferative Implications for Normal Dermal Fibroblast and Breast Cancer Cells - Laura Cianfruglia; Cristina Minnelli; Emiliano Laudadio; Andrea Scirè; Tatiana Armeni (Antioxidants, 2019)
Background: Curcumin is a yellow-orange pigment obtained from the plant Curcuma longa, which is known to exert beneficial effects in several diseases, including cancer. However, at high doses, it may produce toxic and carcinogenic effects in normal cells. In this context, we studied the effects of curcumin on normal human dermal fibroblast (HDF) cells and breast cancer cells (MCF7). Methods: We used cellular viability and growth assays to evaluate the antiproliferative action of curcumin, analyzed the endogenous glutathione levels, conducted cell cycle, apoptosis, and necrosis analyses, and performed immunodetection of glutathionylated and acetylated H3 histones. Results: We found that HDFs are more sensitive to curcumin treatment than MCF7 cells, resulting in pronounced arrest of cell cycle progression and higher levels of cellular death. In both cell types, the homeostasis of the redox cellular environment did not change after curcumin treatment; however, significant differences were observed in glutathione (GSH) levels and in S-glutathionylation of H3 histones. Conclusion: Curcumin administration can potentially confer benefits, but high doses may be toxic. Thus, its use as a dietary supplement or in cancer therapies has a double edge.